Determination of the optimization design parameter for a multi-cavity product in injection molding - 625428 Sharifah Norasyikin Syed Sallehuddin, 1996- author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2019)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Pembuatan)) - Universiti Teknologi Malaysia, 2019